The Effectiveness of the Implementation of Collaborative-Based Academic Supervision by School Principals to Improve the Professionalism of Senior High School Teachers in Sleman Regency - Diah Rina Miftakhi; Sri Sugiyarti (Pustaka Edukasi: Jurnal Pendidikan Indonesia, 2026)
ABSTRACT The effectiveness of teacher professional practice is highly dependent on the competence of the principal in carrying out managerial and instructional tasks, especially in implementing academic supervision programs. Teacher professionalism is essential to achieve educational goals and improve the quality of education. This study aims to examine the level of effectiveness of the implementation of collaborative-based academic supervision. This study uses a qualitative approach using a case study design. Data was collected through observation, interviews, and documentation. The subjects of the study include school principals, teachers, and students. The validity of the data is ensured through triangulation techniques and in-depth observation. The findings show that collaborative academic supervision programs are very effective in improving teachers' professionalism in the teaching and learning process. Principals provide opportunities for teachers to develop a variety of instructional innovations, as teachers are one of the key determinants of the success of learning implementation. Academic supervision has proven to be very effective in improving teacher professionalism. Professional teachers contribute to improving student achievement and improving the overall quality of learning. Keywords: Teacher, Principal, Collaborative, Professionalism, Academic Supervision